Trigamma Series

Evaluate \[\sum_{k=1}^{\infty} \left[ \dfrac{\psi^{(1)} (k) }{k} \right]^{2} \]

ψ(1)(k)\psi^{(1)} (k) is the trigamma function, defined as

ψ(1)(x)=d2dx2[ln(Γ(x))] \psi^{(1)} (x) = \dfrac{\mathrm{d}^2}{\mathrm{d}x^2} [\ln (\Gamma (x) )]


This is a part of the set Formidable Series and Integrals

#Calculus

Note by Ishan Singh
5 years, 3 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

Here's a irrelevant comment:::: (Plagiarized Ishu's work)

Claim: k=1(ψ(1)(k))2=3ζ(3) \displaystyle \sum_{k=1}^\infty ( \psi^{(1)} (k))^2 = 3 \zeta(3) .

Proof:

By writing the trigamma function in terms of integral representation, we have ψ(1)(k)=01lnxxk11xdx \displaystyle \psi^{(1)}(k) = \int_0^1 \dfrac{\ln x \cdot x^{k-1}}{1-x} \, dx . Taking its square gives us

[ψ(1)(k)]2=0101lnxlny(xy)k1(1x)(1y)dxdyk=1[ψ(1)(k)]2=0101lnxlny(1x)(1y)k=1(xy)k1dxdy=0101lnxlny(1x)(1y)(1xy)dxdy=01lnx1x01lny(1y)(1xy)dydx \begin{aligned} \displaystyle \left [ \psi^{(1)}(k) \right]^2 &= & \displaystyle \int_0^1\int_0^1 \dfrac{ \ln x \ln y (xy)^{k-1}}{(1-x)(1-y) } \, dx dy \\ \displaystyle \sum_{k=1}^\infty \left [ \psi^{(1)}(k) \right]^2 &= & \displaystyle \int_0^1\int_0^1 \dfrac{ \ln x \ln y}{(1-x)(1-y)} \sum_{k=1}^\infty (xy)^{k-1} \, dx dy \\ &= & \displaystyle \int_0^1 \int_0^1 \dfrac { \ln x \ln y}{(1-x)(1-y)(1-xy) } \, dx dy \\ &= & \displaystyle \int_0^1 \dfrac{ \ln x}{1-x} \int_0^1 \dfrac{ \ln y }{(1-y)(1-xy) } \, dy dx \end{aligned}

Consider the integral 01lny(1y)(1xy)dy=yy101lny1xydy=A1y101lnyy1dy=B\int_0^1 \dfrac{ \ln y }{(1-y)(1-xy) } \, dy = \displaystyle \dfrac y{y-1} \underbrace{\int_0^1 \dfrac {\ln y}{1-xy} \, dy}_{= \, A} - \dfrac1{y-1} \underbrace{\int_0^1 \dfrac{ \ln y}{y - 1} \, dy}_{= \, B}

Solving for AA gives

01lny1xydy=01lnyx=1(xy)n1dy=n=1xn101lnyyn1dy=n=1xn1n2=Li2(x)x \begin{aligned} \displaystyle \int_0^1 \dfrac {\ln y}{1-xy} \, dy &=& \displaystyle \int_0^1 \ln y \sum_{x=1}^\infty (xy)^{n-1} \, dy \\ &=& \displaystyle \sum_{n=1}^\infty x^{n-1} \int_0^1 \ln y \cdot y^{n-1} \, dy \\ &=& - \displaystyle \sum_{n=1}^\infty \dfrac{x^{n-1}}{n^2} = -\dfrac{ \text{Li}_2 (x)} x \end{aligned}

Similarly, solving for BB gives Li2(1)1=π26 - \dfrac{\text{Li}_2 (1) }1 = - \dfrac{\pi^2}6 .

Thus we have 01lny(1y)(1xy)dy=11x[Li2(x)π26] \displaystyle \int_0^1 \dfrac{ \ln y}{(1-y)(1-xy) } \, dy = \dfrac1{1-x} \left [ \text{Li}_2 (x) - \dfrac{\pi^2} 6 \right ] , and so the double integral becomes

01lnx(1x)2[Li2(x)π26]dx=01ln(1x)x2[Li2(1x)π26]dx \int_0^1 \dfrac {\ln x}{(1-x)^2 } \left [ \text{Li}_2 (x) - \dfrac{\pi^2} 6 \right ] \, dx = \int_0^1 \dfrac {\ln (1-x)}{x^2 } \left [ \text{Li}_2 (1-x) - \dfrac{\pi^2} 6 \right ] \, dx

Because abf(x)dx=abf(a+bx)dx \displaystyle \int_a^b f(x) \, dx = \int_a^b f(a+b-x) \, dx . We integrate by parts with du=ln(1x)x2,v=Li2(x)π26du = \dfrac{ \ln(1-x)}{x^2}, v = \text{Li}_2 (x) - \dfrac{\pi^2} 6 to get

u=0xln(1t)t2dt=(1x)x0xdtt(1t)=ln(1x)ln(x)ln(1x)x u = \int_0^x \dfrac{\ln (1-t)}{t^2} \, dt = -\dfrac{(1-x)}x - \int_0^x \dfrac {dt}{t(1-t)} = \ln(1-x) - \ln(x) - \dfrac{ \ln(1-x)}x

And dvdx=[Li2(x)π26]=lnx1x\dfrac{dv}{dx} = \left [ \text{Li}_2 (x) - \dfrac{\pi^2} 6 \right ] = \dfrac{\ln x}{1-x} .

Integrate by parts gives us

01ln(1x)x2[Li2(1x)π26]dx=01lnx1x[ln(1x)lnxln(1x)x]dx=01lnxln(1x)1xdx=I+01(lnx)21xdx=II+01lnxln(1x)x(1x)dx=III \begin{aligned} \displaystyle \int_0^1 \dfrac {\ln (1-x)}{x^2 } \left [ \text{Li}_2 (1-x) - \dfrac{\pi^2} 6 \right ] \, dx &=& - \displaystyle \int_0^1 \dfrac{ \ln x}{1-x} \left [ \ln(1-x) - \ln x - \dfrac{ \ln(1-x)}x \right ] \, dx \\ &=& -\displaystyle \underbrace{ \int_0^1 \dfrac{ \ln x \ln(1-x)}{1-x} \, dx}_{= \, \rm{I}} + \underbrace{ \int_0^1 \dfrac{ (\ln x)^2}{1-x} \, dx}_{= \, \rm{II}}+ \underbrace{ \int_0^1 \dfrac{ \ln x \ln(1-x)}{x(1-x)} \, dx}_{= \, \rm{III}} \end{aligned}

Now we just need to find the values of I,II\rm{I}, \rm{II} and III\rm{III} . Taking note that B(a,b)B(a,b) is the beta function, we have

I=01lnxln(1x)1xdx=lima0+limb1δδa(δδbB(a,b))=ζ(3)II=01(lnx)21xdx=lima0+limb1δ2δa2(B(a,b))=2ζ(3)III=01lnxln(1x)x(1x)dx=lima0+limb0+δδa(δδbB(a,b))=2ζ(3) \begin{aligned} \displaystyle \rm{I} &=& \displaystyle\int_0^1 \dfrac{ \ln x \ln(1-x)}{1-x} \, dx \\ \displaystyle &=& \displaystyle \lim_{a\to0^+}\lim_{b\to1} \dfrac {\delta}{\delta a} \left( \dfrac {\delta}{\delta b} B(a,b) \right) = \zeta(3) \\ \displaystyle \rm{II} &=& \displaystyle\int_0^1 \dfrac{ (\ln x)^2}{1-x} \, dx \\ \displaystyle &=& \displaystyle \lim_{a\to0^+}\lim_{b\to1} \dfrac {\delta^2}{\delta a^2} \left ( B(a,b) \right) = 2\zeta(3) \\ \displaystyle \rm{III} &=& \displaystyle\int_0^1 \dfrac{ \ln x \ln(1-x)}{x(1-x)} \, dx \\ \displaystyle &=& \displaystyle \lim_{a\to0^+}\lim_{b\to0^+} \dfrac {\delta}{\delta a} \left( \dfrac {\delta}{\delta b} B(a,b) \right) = 2\zeta(3) \end{aligned}

Combining them all together:

01ln(1x)x2[Li2(1x)π26]dx=ζ(3)+2ζ(3)+2ζ(3)=3ζ(3).\displaystyle - \int_0^1 \dfrac {\ln (1-x)}{x^2 } \left [ \text{Li}_2 (1-x) - \dfrac{\pi^2} 6 \right ] \, dx =- \zeta(3) + 2\zeta(3) + 2\zeta(3) = \boxed{3\zeta(3)} .

Pi Han Goh - 5 years, 3 months ago

Log in to reply

Nice one! It doesn't matter if it is plagiarised or not.

Aditya Kumar - 5 years, 3 months ago

Log in to reply

Try solving the actual question! =D

Pi Han Goh - 5 years, 3 months ago

9324ζ(6)\displaystyle \frac{93}{24}\zeta(6)

Ramya Datta - 5 years, 2 months ago

Log in to reply

That's incorrect.

Ishan Singh - 4 years ago

Log in to reply

Hi! Looks like a calculation error (oops! the sum should also contain some $\zeta(3)^2$ term). Anyway, it was solved here http://integralsandseries.prophpbb.com/topic681.html

Ramya Datta - 4 years ago

Log in to reply

@Ramya Datta Nice. I have discovered another solution which allows us to generalize the result to higher powers and other polygamma functions as well.

Ishan Singh - 4 years ago
×

Problem Loading...

Note Loading...

Set Loading...